The Validity and Binding Power of the Parate Execution Clause in the Deed of Granting Mortgage Rights - Febrihadi Suparidho; Ayang Afira Anugerahayu (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Mortgage rights as collateral for land play a significant role in financing practices in Indonesia. One of the main characteristics of mortgage rights is the priority position of the holder and the ease of execution if the debtor defaults. Law Number 4 of 1996 concerning Mortgage Rights on Land and Land-Related Objects (UUHT) introduced the concept of parate execution as regulated in Article 6, which grants the first mortgage holder the right to sell the mortgage object at his own discretion through a public auction if the debtor defaults. In practice, the provisions of Article 6 of the UUHT are outlined and emphasized in the parate execution clause included in the Deed of Granting of Mortgage Rights (APHT). However, questions arise regarding the validity of this clause from a contractual legal perspective and the extent of its binding force on debtors and third parties, considering that the execution process in reality still involves an Auction Institution and its validity is often challenged in court. This study aims to analyze the validity of the parate execution clause in APHT from the perspective of contract law and UUHT, and to examine the binding force of the clause on the parties and third parties. The method used is normative legal research with a statutory approach and a conceptual approach. The results of the study indicate that the parate execution clause is essentially valid and binding as an accessory agreement based on Article 6 of UUHT and the principle of freedom of contract, as long as it does not conflict with public order and is implemented in accordance with auction procedures stipulated by law. However, its implementation cannot be interpreted as a completely independent execution without the involvement of an auction institution and without providing space for debtors to file objections. Parate execution in the context of UUHT is more appropriately understood as the creditor's right to initiate a sale through a public auction with simplified procedures, not as the complete elimination of the control function of the judicial institution. Therefore, it is necessary to affirm the limits of the implementation of parate execution through consistent guidelines and jurisprudence to create a balance between certainty and justice for both creditors and debtors.